Wolf-dogs in Greenland. Interbreeding of Greenland Sled Dogs and Arctic Wolves (Research Note) - Lund Jensen, Manumina; Sinding, Mikkel-Holger (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2023)
This study explores the purposeful interbreeding of Greenland sled dogs and Arctic wolves in Avanersuaq, North Greenland. The paper is based on qualitative data gathered during extensive interviews using North Greenlandic/Polar Inuit dialects and Kalaallisut in North and West Greenland and from relevant literature on the relationships between dog sled driver, sled dog, and Arctic wolf, including genetic studies of Greenland sled dogs. The intent of the study is to understand the human practice of interbreeding sled dogs and wolves in Greenland. Among Greenlanders, it is widely believed that the Greenland sled dog and the Arctic wolf once mated and have had offspring, and that these hybrids have been transformed into Greenland sled dogs. Somehow, today’s storytelling of the wolf-dog is taking the shape of a myth. The question remains: If it did happen, how did it begin and how did it end, and what is the truth behind the story? We thus take a qualitative approach to investigating this phenomenon of the interbreeding of Greenland sled dogs and Arctic wolves. Results show that the Arctic wolf and the Greenland sled dog have indeed crossed paths and have been purposefully interbred, which has resulted in documented cases of wolf-dogs in the sled dog communities of North Greenland.